1966
DOI: 10.1002/hlca.660490126
|View full text |Cite
|
Sign up to set email alerts
|

Die Konstitution von Epoxydon

Abstract: Die Gattung P h w a gehiirt zur IClasse der Fungi Imperfecti, Familie Sphaerioiduceae, und ist bisher erst in wenigen Fallen chernisch untersucht worden. F

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0
5

Year Published

1971
1971
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 15 publications
1
35
0
5
Order By: Relevance
“…Phyllostine (1) and epoxydon (2) are phytotoxic metabolites isolated from the culture filtrate of Phyllosticta sp, a pathogenic fungus of red clover, as the principal toxic compounds causing wilting and simultaneous dark discoloration of leafy stem cuttings of the host plant.l) Epoxydon was also isolated from Phoma sp. as a cytotoxic compound.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Phyllostine (1) and epoxydon (2) are phytotoxic metabolites isolated from the culture filtrate of Phyllosticta sp, a pathogenic fungus of red clover, as the principal toxic compounds causing wilting and simultaneous dark discoloration of leafy stem cuttings of the host plant.l) Epoxydon was also isolated from Phoma sp. as a cytotoxic compound.…”
mentioning
confidence: 99%
“…as a cytotoxic compound. 2 ) Epiepoxydon (3) was initially obtained as a synthetic artifact 3 ) together with epoxydon, and later characterized as a phytotoxin along with epiepoformin (5) from an unidentified fungus, separated from diseased leaves of crapemyrtle (Lagerstroemia indica L.), 4) and then identified as an intermediate in the patulin pathway in Penicillium urticae. 5 ) Epoformin (4) is an antibiotic and cytotoxic compound.…”
mentioning
confidence: 99%
“…which causes marked darkening on the foliage of red clover,!) Among them two phytotoxins, phyllostine (1) and phyllosinol (2) were chemically correlated each other 1bJ and further it was confirmed that phyllosinol is identical with epoxydon which was isolated from phoma sp. .as an antitumor substance.…”
Section: A) Non-selective Synthesis Of Dl-phyllostine'a)mentioning
confidence: 71%
“…which causes marked darkening on the foliage of red clo ver.1) Among them two phytotoxins, phyl lostine (1) and phyllosinol (2) were chemically correlated each other1b) and further it was confirmed that phyllosinol is identical with epoxydon which was isolated from phoma sp. as an antitumor substance.2) Epoxydon has, beside antitumor activity, broad physiological activities, such as stimulation of root elonga tion and antibiotic activity.3) In the present paper, we describe the first synthesis of these two compounds4,5) from 2-hydroxymethyl-1,4-benzoquinone (3).…”
mentioning
confidence: 90%